Language Teacher Assessment Literacy: A Current Review - Nurdiana Nurdiana Nurdiana (Journal of English Language and Culture, 2020)
HHalf of the language teachers’ time is spent on assessing students’ performance. Therefore, they should be literate to language assessment in terms of how to make a good test or knowing which method appropriate to assess their students’ learning. Without having assessment literacy, they may not be able to help their students achieve the best results of their performance. For this reason, the present study attempts to examine language teacher assessment literacy and how it has been measured. Besides, suggestions and recommendations for language teachers regarding assessment literacy are discussed in this study. A literature review was employed to conduct this research. Findings suggest that language teachers need more training on language assessment due to their lack of knowledge of language assessment. Although some of them are assessment literate, they do not practice the knowledge in their classroom. This implies that the training they need could be on how to select appropriate assessments for their students, how to design a test,  alternative assessments, and test specifications.